OPERATION AND EXPANSION OF ROMANIAN AGRICULTURE PRODUCERS GROUPS - Raluca, Ignat; Radu, Voicu; Iuliana, Dobre (Economics of Agriculture, 2012)
In order to develop a model for development of Romanian agriculture is needed study in force and effect legal framework and its application on Romanian agriculture producer groups, to establish legal forms of association and cooperation between producers and processors on pathway product. To achieve this research were used documentation, comparative analysis, synthesis, statistical analysis. Processed data were used in the national legal framework, the National Rural Development Plan 2007-2013, Ministry of Agriculture and Rural Development.